BUILDING LITERARY LITERACY THROUGH LOCAL WISDOM TO DEVELOP STUDENTS' WRITING SKILLS - Wati, Sakdiah (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2024)
Literature, encompassing poetry, prose, and drama, nurtures literary literacy, fostering the understanding and analysis of cultural emotions and thoughts. Language and literature are closely tied to instilling local wisdom, requiring an exploration of Indonesia's national history and dynamics. In the digital era, adeptly packaging local wisdom values globally is imperative for preserving cultural diversity. Integrating local wisdom into education facilitates students' comprehension of their cultural identity, encouraging appreciation for diversity and broadening their global awareness.Writing proficiency involves organizing ideas, developing effective arguments, and composing coherent texts, essential for effective communication in education and various professions. Research focuses on examining how incorporating local wisdom in literature education enhances students' literary literacy and writing prowess. Despite being undervalued in higher education, literature holds significant cultural heritage. The study underscores the impact of integrating local wisdom in literature teaching, fostering students' engagement and inspiring their own literary creations. It emphasizes the pivotal role of local culture in enriching higher education curricula and equipping students with pertinent skills for the future.